PEMANFAATAN NEW MEDIA PADA KEGIATAN LIBRARY ORIENTATION CLASS AND TOUR DI UNIT PELAYANAN TEHNIS PERPUSTAKAAN UNIVERSITAS SYIAH KUALA - Roslina Roslina (SOURCE : Jurnal Ilmu Komunikasi, 2022)
Library Orientation Class and Tour activities at the Library Technical Service Unit, Syiah Kuala University, to introduce new students to understanding procedures for accessing information in the library. Advances in digital technology or often referred to as new media such as computers, telecommunications, the internet, and the world wide web are able to provide better services to users. This is the background for the author to analyze the use of new media in the Library Orientation Class and Tour activities at the University Library Technical Service Unit, Syiah Kuala. The method used in this study is qualitative by conducting observations, interviews, and documentation. The results obtained from this study are the Library Orientation Class and Tour activities at the Syiah Kuala University Library UPT utilizing website media as information access media, Youtube media as educational media, and Zoom media as media that supports virtual tours.